1997
DOI: 10.1074/jbc.272.31.19615
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Protein Components of the Liver Microsomal O2-insensitive NADH-Benzamidoxime Reductase

Abstract: Drugs containing strong basic nitrogen functional groups can be N-oxygenated to genotoxic products. While the reduction of such products is of considerable toxicological significance, most in vitro studies have focused on oxygen-sensitive reductase systems. However, an oxygen-insensitive microsomal hydroxylamine reductase consisting of NADH, cytochrome b 5 , its reductase, and a third unidentified protein component has been known for some time (Kadlubar, F. F., and Ziegler, D. M. (1974) Arch. Biochem. Biophys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
83
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 30 publications
4
83
0
Order By: Relevance
“…In fact, the 2-aminoimidazolinyl moiety can be viewed as a cyclic guanidine 42 and the in vivo reduction of N-hydroxylated guanidines and amidines by microsomes and mitochondria of different organs from different species (e.g., kidney, liver, brain) has been established before. 12,43,44 This result is important because it is compound 16 that showed the highest in vitro BBB permeability in our assays. The respectively), may possibly be attributed to a poor bioactivation.…”
Section: Resultsmentioning
confidence: 92%
“…In fact, the 2-aminoimidazolinyl moiety can be viewed as a cyclic guanidine 42 and the in vivo reduction of N-hydroxylated guanidines and amidines by microsomes and mitochondria of different organs from different species (e.g., kidney, liver, brain) has been established before. 12,43,44 This result is important because it is compound 16 that showed the highest in vitro BBB permeability in our assays. The respectively), may possibly be attributed to a poor bioactivation.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, the reductase activity was dependent on the cofactor NADH and inhibited by potassium cyanide (KCN), whereas typical CYP inhibitors, such as carbon monoxide, were ineffective (6) indicating that the reductase is unlikely to be a cytochrome P450 as was suggested previously (10). Several studies have attempted to identify the third component, and the involvement of stearoyl-CoA desaturase (11) and cytochrome P450 isoenzyme CYP2D (10) in the microsomal fraction as well as a novel molybdenum-containing enzyme in the mitochondrial fraction (12) was suggested.…”
mentioning
confidence: 83%
“…Furthermore, the reductase activity was dependent on the cofactor NADH and inhibited by potassium cyanide (KCN), whereas typical CYP inhibitors, such as carbon monoxide, were ineffective (6) indicating that the reductase is unlikely to be a cytochrome P450 as was suggested previously (10). Several studies have attempted to identify the third component, and the involvement of stearoyl-CoA desaturase (11) and cytochrome P450 isoenzyme CYP2D (10) in the microsomal fraction as well as a novel molybdenum-containing enzyme in the mitochondrial fraction (12) was suggested. In subsequent studies, two highly homologous molybdenum-containing proteins, namely molybdenum cofactor sulfurase C-terminal containing 1 and 2 (MOSC1 and MOSC2, respectively, referred to as mARC1 and mARC2), were shown to display amidoxime reductase activity in vitro when incubated in a reconstituted system with CYB5 and CYB5R3 (cytochrome b 5 reductase 3) (13,14).…”
mentioning
confidence: 83%
“…Cytochrome b 5 , along with its reductase, is an electron transfer protein involved in reduction reactions with methemoglobin (Hultquist and Passon, 1971), oxidized ascorbate (Ito et al, 1981;Shirabe et al, 1995), fatty acid desaturases (Oshino et al, 1971), and some P450 enzymes (Hildebrandt and Estabrook, 1971). Controversy exists, however, over whether these two proteins can directly reduce xenobiotic amidoximes (Kurian et al, 2004) or whether a third P450 or other protein is required for reduction (Clement et al, 1997;Clement and Lopian, 2003;Andersson et al, 2005).…”
mentioning
confidence: 99%
“…In support of the latter, recent metabolism results have demonstrated that CYP1A and CYP3A4 are involved in the oxidative O-demethylations (unpublished). Previous studies with aromatic amidoximes have shown that these functional groups are reduced to amidines by an NADdependent liver microsomal pathway (Clement et al, 1997;Trepanier and Miller, 2000), which includes cytochrome b 5 and NAD cytochrome b 5 reductase (Clement et al, 1997;Clement, 2002;Kurian et al, 2004;Andersson et al, 2005). Cytochrome b 5 , along with its reductase, is an electron transfer protein involved in reduction reactions with methemoglobin (Hultquist and Passon, 1971), oxidized ascorbate (Ito et al, 1981;Shirabe et al, 1995), fatty acid desaturases (Oshino et al, 1971), and some P450 enzymes (Hildebrandt and Estabrook, 1971).…”
mentioning
confidence: 99%